Implementation of the Islamic Economic System in Realizing People's Welfare - Azhari Marhamah; Navissa Briliani Sabilla (Konsultan Jurnal Ilmiah Indonesia, 2025)
This economic system aims to create public welfare by avoiding detrimental practices and promoting actions that are beneficial to all parties involved. The purpose of writing this article is to determine the implementation of the Islamic economic system in realizing public welfare. This type of research is qualitative, the data collected is analyzed qualitatively using thematic analysis techniques. The results of this study are that the economic system is an economic building that is established on the basis of these basic principles that are in accordance with existing environmental and period conditions. Prosperity in the Islamic economic system is the fulfillment of material and non-material needs, the world and the hereafter based on personal and community awareness to obey and obey (be aware) of the laws desired by Allah SWT. through His guidance in the Qur'an, through examples in the exemplary behavior of the Prophet Muhammad SAW, and through ijtihad and the goodness of the scholars.